Tailoring Wettability Control of Superhydrophobic Metallic Surface via Sustainable Fabrication Approach - Jayanth Ivvala (Proceedings)
Introduction: Wetting affects chemical and physical properties. In aluminum, superhydrophobic surfaces keep fog, ice, and corrosion at bay. Biomimicry replicates natural processes. The high surface energy of aluminum limits its intrinsic dewetting properties. Existing surface modification methods have disadvantages, such as hazardous chemicals, high costs, and harsh processing conditions. This work is environmentally friendly and overcomes traditional limitations. Methods: Aluminum alloy plates (AA5083) of commercial grade (ASTM-B-209M) were used in the study. Stationary friction stir processing (sFSP) was carried out on a universal milling machine focused solely on surface characteristics using transition metal powders (99% purity). The prepared samples were polished with abrasive papers to 1000 grit after processing. In the microwave hot water treatment (mHWT), processed and unprocessed samples were processed for 10 min at 800 W. A silanization agent was vapor-deposited on the samples following mHWT at 55 °C for 60 min. Results: The low-strain-rate sFSP of aluminum alloys results in substantial grain refinement, reaching ~1 µm for processed samples and ~30 µm for unprocessed samples. Refined grains have a dense and networked nanostructure after mHWT. After silanization, the samples exhibit excellent contact angles (>155°), low tilt angles (10°), and low contact angle hysteresis (5°). The processed samples, featuring highly refined grains, demonstrate low water adhesion (~16 µN) compared to unprocessed samples (~50 μN), attributed to the high interfacial energy of the Cassie state, effectively entrapping air. These processed samples exhibit remarkable de-wetting properties and mechanical resilience, owing to the strong negative capillary pressure (>1100 kPa) generated by highly dense networked nanostructures. Conclusions: In conclusion, the research helps to develop sustainable and durable superhydrophobic aluminum surfaces. The environmentally friendly and cost-effective strategies explored have far-reaching implications for industrial applications, emphasizing opportunities for advancements and practical utilization across various industries.